Upaya Peningkatan Bed Occupancy Rate Pelayanan Rawat Inap dengan Quantitative Strategic Planning Matrix - Pamungkas, Tegar; Purwadhi; Handayani, Nining (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Quality healthcare services are essential to meet patient needs and compete in the market, supported by reliable resources (Yuniawati et al., 2021). The quality of inpatient services is measured through indicators such as Bed Occupancy Rate (BOR) and Length of Stay (LOS), with an efficient BOR ranging from 60-85% according to the Ministry of Health, while RS Surya Medika PKU Muhammadiyah Sumbawa has 55 beds and a BOR of only 40.34% in 2023, below the established standards (Sudra, 2010). To improve BOR, it is crucial for hospitals to balance the quality of medical services, patient safety, and staff welfare, as well as formulate strategies that consider internal and external factors using tools such as the Quantitative Strategic Planning Matrix (QSPM) to determine appropriate strategic priorities. This research was conducted at RS Surya Medika PKU Muhammadiyah Sumbawa, focusing on inpatient services with a low BOR of 40.34%, compared to the ideal range of 60-85%, and is planned to take place from April to July 2024 using qualitative descriptive methods. The study population includes staff and inpatient patients, with data collection conducted through in-depth interviews, Focus Group Discussions, and direct observations, as well as analysis performed using Gap Analysis, MCUA method, Fishbone Diagram, SWOT analysis, and QSPM to formulate effective alternative strategic planning. The conclusions of this study indicate that several factors influence the Bed Occupancy Rate (BOR) of inpatient services at RS Surya Medika PKU Muhammadiyah Sumbawa, where internal factors affecting BOR include service quality and the completeness of service types. Additionally, external factors such as customer satisfaction and service promotion also play a significant role in attracting more patients. To enhance BOR, RS Surya Medika PKU Muhammadiyah Sumbawa needs to develop the types of services offered, which is expected to meet patient needs and improve their satisfaction, thereby increasing the bed occupancy rate in the hospital. This research is expected to provide significant benefits to RS Surya Medika PKU Muhammadiyah Sumbawa as a preliminary study for the relationship between internal and external factors affecting Bed Occupancy Rate (BOR).